2010
DOI: 10.4103/0250-474x.65017
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of cultural conditions for protease production by a fungal species

Abstract: Studies were carried out on a paddy soil fungal isolate identified to be a strain of Aspergillus niger from Manipal. The parameters that largely impact enzyme production viz., fermentation time, impeller speed, pH, temperature and nutrient supplements were studied. Optimization of production parameters for production of protease was done by the single-parameter mode. Casein served as substrate and proteolytic activity was estimated using Folin-Ciocalteau method at 660 nm. A maximum yield of 71.3 mg tyrosine/g … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Nwagu and Okoli (2011) also observed that a particular strain of Aspergillus fumigatus exhibited maximum mycelial yield and amylase titre at 30°C which is akin to the present findings (Figure 1A), however, the reports of Negi and Banerjee (2010) on A. awamori for production of amylase was not at par with the present finding. As compared to the present study conducted for effect of cultivation time on production of amylase, similar result was reported by Negi and Banerjee (2010) for amylase biosynthesis using A. awamori . Mohamed et al (2011) reported 96 h and 30°C for biosynthesis of amylase which is in accordance with present finding.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Nwagu and Okoli (2011) also observed that a particular strain of Aspergillus fumigatus exhibited maximum mycelial yield and amylase titre at 30°C which is akin to the present findings (Figure 1A), however, the reports of Negi and Banerjee (2010) on A. awamori for production of amylase was not at par with the present finding. As compared to the present study conducted for effect of cultivation time on production of amylase, similar result was reported by Negi and Banerjee (2010) for amylase biosynthesis using A. awamori . Mohamed et al (2011) reported 96 h and 30°C for biosynthesis of amylase which is in accordance with present finding.…”
Section: Discussionsupporting
confidence: 82%
“…Even though, the outcome of this study could not specify the genuine moisture content in the system, however, it gave a clue of the preliminary water content of PM which was essential to attain the maximum fungal growth and biosynthesis of enzyme. While working with Aspergillus species and A. awamori , Chimata et al (2010), Negi and Banerjee (2010) reported 70 and 90% humidity for amylase production which is at par with the present finding obtained with A. terreus NCFT 4269.10.…”
Section: Discussionsupporting
confidence: 74%
See 3 more Smart Citations